The CARL Library Impact Framework - Mark Robertson; Tania Gottschalk; Justine Wheeler (Partnership: The Canadian Journal of Library and Information Practice and Research, 2024)
In December 2021, the Canadian Association of Research Libraries (CARL) released the CARL Library Impact Framework (CLIF).  While library impact has been a topic of discussion for many years, CLIF offers a new contribution to the dialogue on the demonstration of impact of research libraries.  The concept of impact pathways was borrowed from the Federation for the Humanities and Social Sciences report entitled Approaches to Assessing Impacts in the Humanities and Social Sciences.  To realize the impact pathways concept, CLIF has adapted a logic model framework.  This approach provides users of CLIF with a way to represent a more complete arc of influence of research libraries systematically and visually. By design, CLIF encourages the use of assessment techniques and tools beyond the quantitative data collection and descriptive statistics often used by research libraries. This paper provides an overview of CLIF, its genesis, intent, structure, and possibilities for its application in research libraries.